Vaccination with cyclin-dependent kinase tick antigen confers protection against Ixodes infestation - Gomes, H.; Moraes, J.; Githaka, Naftaly W.; Martins, R.; Isezaki, M.; Silva Vaz, I. da; Logullo, C.; Konnai, S.; Ohashi, K. (Elsevier, 2015)
Among arthropods, ticks lead as vectors of animal diseases and rank second to mosquitoes in transmitting human pathogens. Cyclin-dependent kinases (CDK) participate in cell cycle control in eukaryotes. CDKs are serine/threonine protein kinases and these catalytic subunits are activated or inactivated at specific stages of the cell cycle. To determine the potential of using CDKs as anti-tick vaccine antigens, hamsters were immunized with recombinant Ixodes persulcatus CDK10, followed by a homologous tick challenge. Though it was not exactly unexpected, IpCDK10 vaccination significantly impaired tick blood feeding and fecundity, which manifested as low engorgement weights, poor oviposition, and a reduction in 80% of hatching rates. These findings may underpin the development of more efficacious anti-tick vaccines based on the targeting of cell cycle control proteins.